2000
DOI: 10.1123/jsep.22.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Expert-Novice Differences in Planning Strategies during Collegiate Singles Tennis Competition

Abstract: Research examining planning strategies used by high-strategy open-skill performers is limited. This study examined planning responses of collegiate varsity (experts, n = 6) and beginner (novices, n = 6) women tennis players between points during competition. Other articles focused on expert-novice differences in problem representations (quantitative analyses of verbal data via audiotaping) accessed during simulated situations and during actual competition (immediate recall point interviews) and performance ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
133
1
21

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 0 publications
7
133
1
21
Order By: Relevance
“…Findings from the present study showed similar results according to age group and player's specific experience, which was somewhat expected since usually the most experienced players play in adult teams. Indeed, adult teams and more experienced players presented more goal concepts, in agreement with previous studies [10,18], in which more experienced players also presented more goal concepts. However, in tennis experts and novices have been shown to generate a similar number of goal concepts [8,9].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Findings from the present study showed similar results according to age group and player's specific experience, which was somewhat expected since usually the most experienced players play in adult teams. Indeed, adult teams and more experienced players presented more goal concepts, in agreement with previous studies [10,18], in which more experienced players also presented more goal concepts. However, in tennis experts and novices have been shown to generate a similar number of goal concepts [8,9].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have differentiated experts from novices mainly through divergences in age, years of experience, competition experience and players' ranking in their leagues [8][9][10]. In spite of the analysis of the extreme groups (i.e., experts and novices) having promoted valuable information to the research and practical domain this approach presents some limitations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations